Debt financing and technological innovation: evidence from China - Xin, Kuang; Sun, Yuchun; Zhang, Ran; Liu, Xiao (Journal of Business Economics and Management, 2019)
The availabilities of debt for Chinese firms have been increased since 2008 due to the expansionary monetary policies. These policies triggered concerns over the impact of debt financing on firms’ technological innovation activities. Based on a sample of 225 listed computer and telecommunications equipment firms in China within 2008-2015, this study explored the effect of debt financing on two types of technological innovation, namely radical and incremental innovation. Specifically, both the direct effect of debt financing on technological innovation and its moderating effect on the relationship between R&D intensity and technological innovation were investigated. Results of this study reveal that radical innovation decreases with debt financing at decreasing rates, while incremental innovation is not affected by debt financing itself. In addition, debt financing interacted with R&D intensity exerts positive effect on both radical and incremental innovation. This study adds meaningful insights to the literature on financing technological innovation and builds a bridge connecting macroeconomic policies to firm activities.